A freestanding hydroxylated carbon nanotube film boosting the stability of Zn metal anodes. (August 2022) - Huang, Jian-Qiu; Hou, Zhen; Gao, Peisen; Yan, Xiaofeng; Lin, Xiuyi; Zhang, Biao
Abstract: Carbon film has been widely adopted to improve the stability of Zn metal anode for rechargeable aqueous Zn-ion batteries. Serving as a buffer layer between the anode and separator, the carbon film reduces the localized current density for suppressing the dendrite initiation. Yet, the zincophobic nature of carbon counteracts its effectiveness. Herein, a freestanding hydroxylated carbon nanotube (OH-CNT) film is adopted as the buffer layer, where the abundant hydroxyl groups provide zincophilic sites for stable Zn deposition. Furthermore, the conductive and porous CNT film homogenizes the ion and electron distribution for smooth Zn growth. Consequently, the symmetric cell with Zn/OH-CNT electrode exhibits a dendrite-free morphology and delivers superior performance with a low overpotential of 83 mV after 500 h plating and stripping process. The beneficial effects of OH-CNT film on boosting the electrode stability are confirmed in the full cell by coupling with a modified Znx V2 O5 ·H2 O cathode. This study emphasizes the essential roles of surface functionality of carbon buffer layers, where hydroxyl groups display merit. Graphical Abstract: A freestanding hydroxylated carbon nanotube film is developed as a buffer layer for protecting Zn metal anode from dendrite growth. The conductive and porous film facilitates fast ion and electron transport and the hydroxyl groups attached on carbon nanotubes provide abundant zincophilic sites for homogenous Zn deposition. ga1